2022
DOI: 10.22605/rrh7152
|View full text |Cite
|
Sign up to set email alerts
|

A rural community’s perspective on the causes of and solutions to the opioid crisis in southern Virginia: a qualitative study

Abstract: Introduction: Opioid use disorder is a leading public health issue in the USA, with complex drivers requiring a multi-level response. Rural communities are particularly affected by opioid misuse. Due to variability in local conditions and resources, they require community-specific responses. The aim of this study was to gain insight into the perceptions, knowledge, and experiences of members of a rural community impacted by the opioid crisis to inform the development of local strategies to address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…A few family members and CBO staff in our research were reportedly active in helping to address a few policies and practices that were not helpful such as providing access to a phone in instances where a phone was necessary to access a treatment space. These findings add to the body of literature on family and CBO support for PWUS when accessing treatment, including literature which indicates that these groups sometimes help with providing transportation to treatment [42][43][44][45]. According to the literature, providing support may have personal impacts on those providing the support, and research has found, for example, that some family members report physical and mental health issues (e.g.…”
Section: Discussionmentioning
confidence: 53%
“…A few family members and CBO staff in our research were reportedly active in helping to address a few policies and practices that were not helpful such as providing access to a phone in instances where a phone was necessary to access a treatment space. These findings add to the body of literature on family and CBO support for PWUS when accessing treatment, including literature which indicates that these groups sometimes help with providing transportation to treatment [42][43][44][45]. According to the literature, providing support may have personal impacts on those providing the support, and research has found, for example, that some family members report physical and mental health issues (e.g.…”
Section: Discussionmentioning
confidence: 53%